2023
DOI: 10.1039/d2lc00871h
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic sorting of microfluidic droplets at kHz rates using optical absorbance

Abstract: Droplet microfluidics allows one to address the ever-increasing demand to screen large libraries of biological samples. Absorbance spectroscopy complements the established fluorescence detection by alternative target identification and providing quantifiable...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Also, since the sorting uses Arduino-like microcontrollers, improvement in hardware will result in increased computation speed while retaining the accessibility of being inexpensive and open-source. Complementary work by Richter et al has shown an increased sorting throughput and removal of droplet trace artifacts by using a combination of surface acoustic waves and microlenses in the form of an optical air cavity. We envision that a further upgrade to AADS designs could incorporate design improvements from both studies.…”
Section: Discussionmentioning
confidence: 99%
“…Also, since the sorting uses Arduino-like microcontrollers, improvement in hardware will result in increased computation speed while retaining the accessibility of being inexpensive and open-source. Complementary work by Richter et al has shown an increased sorting throughput and removal of droplet trace artifacts by using a combination of surface acoustic waves and microlenses in the form of an optical air cavity. We envision that a further upgrade to AADS designs could incorporate design improvements from both studies.…”
Section: Discussionmentioning
confidence: 99%
“…Then the droplet is forced into the collection channel. 120,121 In addition, a membrane valve can also be used to sort the droplets. The valve is pressurized to squeeze the waste channel and increase its resistance.…”
Section: Droplet Manipulationmentioning
confidence: 99%
“…Attempts to increase the sensitivity and sensitivity of absorbance sorting have been made: (i) Duncombe et al introduced UVADS (UV–Vis Spectra Activated Droplet Sorter) in a channel design with increased path length (by installing a right-angled turn at the detection interface) and by recording entire spectra (200–1050 nm) as unique signatures in UV–Vis Spectra-Activated Droplet Sorting. (ii) Richter et al . have shown kHz sorting throughput in a model separation based on removal of droplet trace artifacts by using a combination of surface acoustic waves and microlenses in the form of an optical air cavity.…”
Section: Detection and Sortingmentioning
confidence: 99%
“…128 Attempts to increase the sensitivity and sensitivity of absorbance sorting have been made: (i) Duncombe et al 206 introduced UVADS (UV−Vis Spectra Activated Droplet Sorter) in a channel design with increased path length (by installing a rightangled turn at the detection interface) and by recording entire spectra (200−1050 nm) as unique signatures in UV−Vis Spectra-Activated Droplet Sorting. (ii) Richter et al 207 have shown kHz sorting throughput in a model separation based on removal of droplet trace artifacts by using a combination of surface acoustic waves and microlenses in the form of an optical air cavity. (iii) Medcalf et al 208 overcame the scattering caused by droplet edges in an improved microfluidic design (i.e., with a single-layered inlet leading to enabling more even spacing), refractive index matching, and faster sorting algorithms (compared to ref 128), so sorting around 1 kHz became possible.…”
Section: Detection and Sortingmentioning
confidence: 99%